A STUDY ON TRANSGENDER AWARENESS ABOUT EDUCATIONAL FACILITIES AND ITS IMPACT ON SOCIAL CHANGE - Rabbul Hussain, Deepshikha Bharadwaz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Man and woman both are the two parts of life, without them we cannot think a biological life. On the basis of the biological aspect we have these two gender view, but there is another type to which we cannot deny and it is called transgender. They are known as third gender. It describes people whose gender identity may not match the sex they were assigned at birth. They have their different gender identity. Gender diversity is deeply rooted in India. Transgender individuals in India have a greater historical importance. Though before twenty century they were deprived from their basic needs and rights but after that whole country has realized their needs. From that period it is tried to erase the deeply rooted social stigma and prejudices that they faces from the many years. It is realized that education is the way by which they can be aware about their rights and duties. Now-a-days educational opportunities must be given to the third gender society just like other recognized minority groups. The group has a very significant contribution in the process of social change. In this paper I am going to study the awareness about the educational facilities of transgender and its impacts on social change in Kamrup (M) District, Assam, NER. It is a study where descriptive study method with primary data used. Finally effort is made to give some suggestions by concentrating in this paper.